THE CHARACTERISTIC OF COASTAL SUBSURFACE QUARTENARY SEDIMENT BASED ON GROUND PROBING RADAR (GPR) INTERPRETATION AND CORE DRILLING RESULT OF ANYER COAST, BANTEN PROVINCE - Kris Budiono (Marine Geological Institute of Indonesia, 2013)
The study of characteristic of subsurfase Quatenary sediment of Anyer coast have been done by using the data of Ground Probing Radar (GPR) image, Surfacial Geological map around the coast and the result of core drilling. The GPR equipment which was used are GSSI SIR 20 system and GSSI Sub Echo 40 MHz antennas. The GPR data image have been processed by using Radan GSSI software, Window NTIM version. The processing including Stacking, Spatial Filter, Migration and Decompolution. The interpretation of GPR image was done by using the principle of GPR stratigraphy through recoqnize to the internal and external reflector such as reflector configuration, continoutas, reflection, amplitude, etc, Furthermore the interpretation result of GPR image are correlated with the surfacial geological map and core drilling result that have been done by previous researscher. Besed on that correlation result, the characteristic of subsurface Quatenary deposits of study area can be divided into 5 unit mainly unit A, B, C, D and E. Unit A is the uppermost layer which is charactized by clay layer and coral reff fragments. Below the unit A they are unit B, C, and D wich were characterized by intercalation between sand and clay, sand deposit or sandstone, loose to dense. This condition is shown by the SPT (Standard Penetration Test) which have range between 10 to 50 blows per 15 Cm. Based on the characteristic of GPR image and sediment deposits of core drilling, these sediment deposits are interpreted as coastal and shallow water sediment deposits. Unit E is the lowermost layer which is interpreted as volcanic deposit. Keywords: subsurface quatenary sediment, ground propbing radar, core drilling, Anyer coast. Penelitian karakteristik sedimen bawah permukaan Kuarter di kawasan pantai Anyer telah dilakukan dengan mempergunakan data citra â€œ Ground Probing Radarâ€, geologi permukaan di sekitar kawasan pantai dan data hasil pemboran inti. Peralatan GPR yang dipergunakan adalah sistim SIR 20 GSSI dan antenna MLF 3200 GSSI.Data citra GPR telah diproses dengan mempergunakan perangkat lunak RADAN GSSI versi window NTIM. Pemrosesan terdiri dari â€œStackingâ€, â€œSpatial Filterâ€, â€œMigrationâ€ dan â€œDecompolutionâ€. Penafsiran Citra GPR dilakukan dengan mempergunakan prinsip Stratigrafi GPR melalui pengamatan terhadap internal dan eksternal reflector seperti konfigurasi reflector, kontinuitas, refleksi, amplitude dan lain-lain. Selanjutnya hasil penefsiran citra GPR ini dikorelasikan dengan peta geologi permukaan dan hasil pemboran inti yang telah dilakukan oleh peneliti terdahulu. Berdasarkan hasil korelasi tersebut karakteristik endapan Kuarter bawah permukaan daerah penelitian dapat dibagi menjadi 5 unit yaitu Unit A, B, C, D dan E. Unit A merupakan unit paling atas yang dicirikan lapisan lempung dan kerakal kerikil hasil rombakan koral. Unit B, C dan D berada di bawah ubit A yang merupakan endapan selang seling pasir dan lempung serta endapan pasir atau batu pasir bersifat urai sampai padat. Kondisi ini ditunjukan oleh hasil pengujian SPT(â€œStandard Penetration Testâ€) yang berkisar antara 10 sampai lebih dari 50 tumbukan per 15 Cm.Berdasarkan karakteristik fasies citra GPR dan endapan sedimen dari hasil pemboran inti, endapan sedimen tersebut ditafsirkan sebagai endapan pantai dan endapan laut dangkal Unit E merupakan lapisan paling bawah yang ditafsirkan sebagai endapan gunung api. Kata kunci: Sedimen Kuarter bawah permukaan,â€Ground Probing Radarâ€, pemboran inti, pantai Anyer